Combination of Pandan (Pandanus Amaryllifolius) Extract and Dragon Fruit (Hylecereus Polyhizus) Pulp for Jam Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Leaves of Pandanus amaryllifolius are used as natural colourant due to presence of high chlorophyll content. Not only dragon fruits or pitayas (Hylocereus sp.) are believed to be rich in antioxidants but also they have high economic potential in domestic and foreign market. In order divesify different products from these sources, a research was conducted to combine pandan extract and pitaya pulp for jam production. The search focused on the effect of modified starch concentration, ratio of pandan extract: pitaya pulp, sugar supplementation, temperature and time during condensation to the shear stress and appearance of jam. Results showed that 1.5% modified starch, 3% of pandan extract: pitaya pulp, 10% sugar supplementation, 95oC and 10 minutes during condensation will give the best quality of jam.Keywords: Pandan, Dragon fruit, Modified starch, Sugar, Condensation, Jam.